Contemporary Human Rights Oppression against the Rohingya: A Fiduciary Theoretical Analysis of Humanitarian Intervention Prospects - Bama Andika Putra (Budapest International Research and Critics University, 2022)
Human rights oppressions continue to take place against the Rohingya people in Myanmar. Despite the presence of crimes against humanity, genocide, and mass murders, the United Nations Security Council continues to display divergence in how to respond to the crisis appropriately. This article aims to illustrate the legal basis, structure, and extent of state authority in utilizing force in response to gross human rights violations against the Rohingya people by employing Criddle's 2015 fiduciary theory of humanitarian intervention. This article concludes the following steps to be undertaken; 1) collectively determine that the Rohingya people have been prosecuted in the form of genocide, crimes against humanity, and mass murder, to transfer the responsibility to protect towards the global community, 2) interventions need to honor the domestic preferences of the Myanmar people and government, to sustain an acceptable humanitarian intervention, and 3) construct clear parameters that would induce the imposition of humanitarian intervention.